IMPLICATIONS OF SHARIA ECONOMIC LAW FOR HALAL CERTIFICATION ON IMPORTED PRODUCTS IN INDONESIA - Rismilda, Nela Aprilia; Supangat, Supangat (istinbath, 2024)
The rapid flow of globalization certainly impacts aspects of life, including the increasingly accessible economic aspect. The magnitude of free trade results in various products entering a country without strict supervision in terms of quality. Indonesia is a country with high export-import activities; this can be seen based on data from the Badan Pusat Statistik (BPS) on Imports of Beef from 2017 to 2021, which shows an increase every year. The size of imported products entering Indonesia is necessary to monitor and check the halalness of these products, considering that the majority of the population in Indonesia is Muslim. This study aims to analyze the position of halal certification of imported goods or products based on the perspective of Sharia economic law. This research uses qualitative methods with data collection techniques and literature study. The results show that the position of halal certification of imported products based on the perspective of sharia economic law has a central position as stated in the Qur'an, some hadiths of the prophet, and other sources of Islamic law for which none of these sources of law reject the existence of halalness to what Muslims need. In addition, the position of halal certification of imported goods in terms of Sharia economic law is also seen as an effort to be in harmony with Islamic teachings, which aim to bring maslahah, not mafsadah, to the people who consume.